2014
DOI: 10.1586/17446651.2014.911083
|View full text |Cite
|
Sign up to set email alerts
|

The changing epidemiology of congenital hypothyroidism: fact or artifact?

Abstract: Screening increases prevalence estimates for most diseases and congenital hypothyroidism (CH) is no exception, affecting one in 6700 children by clinical ascertainment and one in 3500 in the first surveys of systematic biochemical screening of newborns. Importantly, screening has resulted in the disappearance of intellectual disability due to CH. A further doubling in prevalence estimates has recently been reported, mostly accounted for by changes in screening algorithms; accordingly, the prevalence of overt C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 58 publications
0
9
1
Order By: Relevance
“… 5 Now this range stands at 1:4000 after congenital screening programs were instituted. 6 In developing countries, newborn screening (NS) is mandatory. However in countries like Pakistan no Newborn Screening program has been started yet.…”
Section: Introductionmentioning
confidence: 99%
“… 5 Now this range stands at 1:4000 after congenital screening programs were instituted. 6 In developing countries, newborn screening (NS) is mandatory. However in countries like Pakistan no Newborn Screening program has been started yet.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 The ratio of FPs to true positives for CH is estimated at 15:1, 7 with global recall rates ranging from 0.01% to 13.3%. 1 Whether lowering of TSH thresholds identifies additional cases of CH that will benefit from treatment, or rather primarily increases screening costs, detection of transient, mild or subclinical hypothyroidism, 5,8,9 or clinically insignificant 'disease', 3 has long been disputed. Alm et al 10 retrospectively tested 100,239 stored blood spots collected in Sweden during the 1970s, before the initiation of screening for CH, then followed up the records of 31 of 32 infants with TSH > 20 mU/L whole blood.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 There has been an increase in the reported prevalence of congenital hypothyroidism because of the improvements in neonatal medicine and inborn screening programs, as well as the increased sensitivity of testing methods. 3,5 Deladoëy et al reported an increase from 1 in 6700 children to 1 in 3500 children in their review regarding the condition, worldwide. 5 In Africa, studies in Nigeria have shown varying incidence between 16.4% and 1.4%.…”
Section: Introductionmentioning
confidence: 99%
“…3,5 Deladoëy et al reported an increase from 1 in 6700 children to 1 in 3500 children in their review regarding the condition, worldwide. 5 In Africa, studies in Nigeria have shown varying incidence between 16.4% and 1.4%. 6,7 However, a lower incidence (0.1%) was reported in South Africa.…”
Section: Introductionmentioning
confidence: 99%